Karrikins: Regulators Involved in Phytohormone Signaling Networks during Seed Germination and Seedling Development - Meng, Yongjie; Shuai, Haiwei; Luo, Xiaofeng; Chen, Feng; Zhou, Wenguan; Yang, Wenyu; Shu, Kai (Frontiers in Plant Science, 2017)
Seed germination and early seedling establishment are critical stages during a plant’s life cycle. These stages are precisely regulated by multiple internal factors, including phytohormones and environmental cues such as light. As a family of small molecules discovered in wildfire smoke, karrikins (KARs) play a key role in various biological processes, including seed dormancy release, germination regulation and seedling establishment. KARs show a high similarity with strigolactone (SL) in both chemical structure and signaling transduction pathways. Current evidence shows that KARs may regulate seed germination by mediating the biosynthesis and/or signaling transduction of abscisic acid (ABA), gibberellin (GA) and auxin (IAA). Interestingly, KARs regulate seed germination differently in different species. Furthermore, the promotion effect on seedling establishment implies that KARs have a great potential application in alleviating shade avoidance response, which attracts more and more attention in plant molecular biology. In these processes, KARs may have complicated interactions with phytohormones, especially with IAA. In this updated review, we summarize the current understanding of the relationship between KARs and SL in the chemical structure, signaling pathway and the regulation of plant growth and development. Further, the crosstalk between KARs and phytohormones in regulating seed germination and seedling development and that between KARs and IAA during shade responses are discussed. Finally, future challenges and research directions for the KAR research field are suggested.